2013
DOI: 10.1248/bpb.b12-00760
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Ketamine and Pregabalin at Sub-effective Doses Synergistically Reduces Neuropathic Pain without Motor Dysfunction in Mice

Abstract: Peripheral or central nerve injury often leads to neuropathic pain. Although ketamine and pregabalin are first line options for the treatment of neuropathic pain, their clinical application is limited due to side effects such as sedation, dizziness and somnolence. We designed this study to determine whether the intrathecal (i.t.) co-treatment with ketamine and pregabalin at sub-effective low doses would elicit a sufficient pain relief without producing side effect in a neuropathic pain mouse model. At day 7 af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Many studies indicate that low-dose NMDA receptor antagonist ketamine can prevent remifentanil-induced hyperalgesia, suggesting that NMDA receptors are related to the mechanism of OIH (Hang et al, 2011;Joly et al, 2005). However, the clinical application of ketamine to prevent hyperalgesia is limited because of side effects such as somnolence, dizziness and sedation (Lim et al, 2013). Furthermore, blockade of NMDA receptor function may affect the normal physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicate that low-dose NMDA receptor antagonist ketamine can prevent remifentanil-induced hyperalgesia, suggesting that NMDA receptors are related to the mechanism of OIH (Hang et al, 2011;Joly et al, 2005). However, the clinical application of ketamine to prevent hyperalgesia is limited because of side effects such as somnolence, dizziness and sedation (Lim et al, 2013). Furthermore, blockade of NMDA receptor function may affect the normal physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical application of ketamine to prevent hyperalgesia is limited because of side effects such as somnolence, dizziness and sedation [27]. …”
Section: Discussionmentioning
confidence: 99%
“…ketamine intrathecally had no effect on postoperative analgesia [27]. Rota rod test revealed that motor dysfunction was found with the use of i.t.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25) We have also used the rota-rod test for mice to examine the potential sedative effects of clonidine. 26) The Roto-rod apparatus (model# DJ-4009; Dae-Jong Engineering & Clean Technology, Seoul, Korea) consisted of a rotating horizontal bar (diameter=6 cm), which was subdivided into 4 compartments by rotating plates.…”
Section: Rota-rod Testmentioning
confidence: 99%